A synonymous mutation in IGF-1 impacts the transcription and translation process of gene expression - S.Y. Wang; Y.Y. Cheng; S.C. Liu; Y.X. Xu; Y. Gao; C.L. Wang; Z.G. Wang; T.Q. Feng; G.H. Lu; J. Song; P.J. Xia; L.L. Hao (Molecular Therapy: Nucleic Acids, 2021)
Insulin-like growth factor 1 (IGF-1) is considered to be a crucial gene in the animal development of bone and body size. In this study, a unique synonymous mutation (c.258 A > G) of the IGF-1 gene was modified with an adenine base editor to observe the growth and developmental situation of mutant mice. Significant expression differences and molecular mechanisms among vectors with different alanine synonymous codons were explored. Although modification of a single synonymous codon rarely interferes with animal phenotypes, we observed that the expression and secretion of IGF-1 were different between 8-week-old homozygous (Ho) and wild-type (WT) mice. In addition, the IGF-1 with optimal codon combinations showed a higher expression content than other codon combination modes at both transcription and translation levels and performed proliferation promotion. The gene stability and translation initiation efficiency also changed significantly. Our findings illustrated that the synonymous mutation altered the IGF-1 gene expression in individual mice and suggested that the synonymous mutation affected the IGF-1 expression and biological function through the transcription and translation processes.